Karakter Morfofisiologi dan Agronomi Kedelai Toleran Salinitas - Runik Dyah Purwaningrahayu (Puslitbang Tanaman Pangan, 2016)
Salt tolerant cultivar of soybean is considered more economical to anticipate the spread of land salinity. Increased salinity in agricultural lands occurred in several places in Indonesia, resulted from the contamination of irrigation water, excessive uses of fertilizers, sea water intrusion and drought stress. To breed the salt tolerant soybean cultivars required knowledge of specific morpho-physiological and agronomical characters which can be used as an indicator of soybean genotypes tolerance to salinity stress. Researchers classified soybeans according to their degree of tolerance to salinity stress, namely sensitive, moderate, and tolerance based on plant characters such as: emergency ability, growth and survival rate, the degree of toxicity due to salt, K+, Na+ and Cl- concentration in plant tissues, prolines accumulation, electrolyte leakage rates, water content of plant, plant biomass and seed yield or reduced seed yield. Soybean genotypes which could grow and produce seed in soil with the salinity levels of above 5 dS/m is considered as having potential for the tolerant varieties.